Translation and Cultural Adaptation of Multi-Attribute Utility Instrument (MAUI) Indonesian Version of the 15D Questionnaire - Dian Parwati; Libriansyah; Gesnita Nugraheni; Yunita Nita (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder that cannot be cured and progressively develop into a complication affecting the patient's health-related quality of life (HRQoL). The utility is a measure of preference-based HRQoL. Indirect utility measurements can be measured using the Multi-Attribute Utility Instrument (MAUI) instrument, one of which is the 15D questionnaire that has never been translated and adapted culturally in Indonesian. Objective: Translating and culturally adapting the 15D questionnaire to Indonesian diabetes mellitus patients. Methods: The translation process was carried out through the stages of forward translation, reconciliation, and backward translation involving two qualified translators and three experts in their field. The pilot test stage involved eight respondents consisting of 6 diabetes mellitus patients and two healthy individuals. Results: Problems in the linguistic validation process led to more conformity of word equivalents from the original to the target language. The agreement found was in the area of semantic equivalence, idiomatic equivalence, and experiential equivalence. The problem was resolved by reconciliation during the Focus Group Discussion, which translators and experts in their field attended and discussed with the original author to get equality of meaning in terms of language and culture. The Indonesian version of the 15D questionnaire tested on eight respondents showed results that were easy to understand and straightforward. Conclusion: The Indonesian version of the 15D questionnaire is valid from the linguistic and cultural adaptation stage. Further research is needed relating to the validation and reliability of the questionnaire.